The Correlation Between Vocabulary Mastery and Student’s English Interest Toward Student’s Speaking Achievementat SMP Negeri 44 Satap OKU - Nurul Afifah (Journal of Language Education (JoLE), 2018)
The objective of this study was to find out the correlation between vocabulary mastery and student’s English interest toward speaking ability of the second grade students of SMP NEGERI 44 SATAP OKU; the design of the study was correlational design; to find out the problem of the study. The population of the study is all of the second grade students that have 4 classes VIIIA, VIIIB, VIIIC and VIIID with the total number 125 students and the sample is taken by using sample size to determine the number of the sample based on table of sample size, the writer got 79 students at 99% confidence level from 125 students. The data collected by using test and questionnaire, there are 2 types of test to measure the students’ ability in mastering vocabulary and students speakingability and questionnaire is used to collect the data of English interest. The techniques used to analyze the data are multiple correlation and regression by using SPSS 20, normality, homogeneity and linearity. The results of the study show that there is a positive correlation between vocabulary mastery and speaking ability toward student’s English interest, both partially and simultaneously. The positive correlation indicates that vocabulary mastery and student’s English interest tend to go up or to go down altogether with Speaking Ability